Pengaruh Viskositas Cat Terhadap Daya Lekat Bahan Pelapis Akhir pada Kayu Rajumas (Duabanga moluccana Blume): The Effect of Paint Viscosity on The Adhesion of Top Coating on Rajumas Wood (Duabanga moluccana Blume) - Liza Umitasari; Anwar, Hairil; Lestari, Andi Tri (PERENNIAL, 2023)
This research aims to analyze the effect of paint viscosity on the adhesion of the final coating material to the radial and tangential sections of Rajumas wood. The research samples were smoothed using sandpaper and coated with water-based paint. Variations in paint viscosity are obtained by dilution using 10%, 20% and 30% of 1L of water. The viscosity of the paint solution obtained by dilution of 10%, 20% and 30% was 2.32 poise, 2.41 poise and 2.44 poise, respectively. Paint adhesion testing uses the Cross Cut Test method which refers to ASTM D 3359-09. The results of the research show that variations in paint viscosity have a significant effect on the adhesion of the final coating material to the radial and tangential cross-sections of Rajumas wood. A viscosity of 2.32 poise produces the best paint adhesion compared to a viscosity of 2.41 poise and 2.44 poise and the difference in cross-section (radial and tangential) does not show a significant difference in the adhesion value of the final coating material to Rajumas wood.